Organic piperazine p-nitrophenol (PPN) single crystal growth and characterization. (2021) - Rathika, A.; Antony Lilly Grace, M.; Arun kumar, A.; Subramaniyan, R.; Suja, R.
Highlights: Good optical quality was grown at room temperature using methanol as a solvent. The band gap of the PPN crystal is Eg = 3.8 eV. The SHG efficiency of the PPN crystal is 0.59 times that of the KDP. The microhardness value of n = 4 indicates that the crystal belongs to the soft material group. Abstract: The monitored conventional solution growth technique was used to develop organic piperazine p-nitrophenol (PPN) single crystals. The crystal system and lattice parameters of PPN were confirmed using powder single crystal X-ray analysis. FTIR spectroscopy used to investigate functional groups of PPN. A UV–vis-NIR analysis was performed to examine the cut-off wavelength and the optical operating window. The bandgap of the material was measured. Thermogravimetric and Differential Thermal Analysis measurements was used to determine the thermal characteristics of PPN crystal. At room temperature, the Vickers microhardness test was used to determine mechanical stability. The results of hardness were examined using Meyer's law. The Kurtz and Perry powder method is used to measures the Second Harmonic Generation of PPN crystals.